Researchers and practitioners as co-designers of a learning environment in Biotechnology - Iolie Nicolaidou; Kyza, Eleni A. (My University, 2009)
There is a need to create learning communities of researchers and practitioners for designing motivating and sustainable curricula in science education. This work examines the process of participatory design of a diverse design team, consisting of two researchers and three educators, as they collaborated in developing an innovative web-based inquiry learning environment on the socio-scientific issue of genetically modified organisms. The data collected came from ten two-hour meetings and took the form of field notes, artifacts and videotapes of the meetings, which were later transcribed. The data were analyzed qualitatively, following grounded theory design, with coding and analysis focusing on identifying the challenges each team member faced and the tensions created along the design process. The analysis identified several challenges. Findings point to the need for structuring co-design experiences around activities for building common ground, initiating new members to the process of design, and helping them get acquainted with the rules of the game, especially when the work involves innovative software environments which challenge long established ideas about the teaching of science. A surprising finding was the strong disagreement, between the biologists, about the methodological approach in selecting the data for the inquiry environment. This tension was created by different views on the Nature of Science held by each teacher and points to the need to build such discussions into the frame of work of collaborative and participatory design teams.
Keywords: Biotechnology; Web-based learning environment; Inquiry; Socio-scientific issues